Sosialisasi Pencegahan Cidera Ergonomi untuk Meningkatkan Kesehatan dan Produktivitas Pemuda Busan Korea Selatan - Adiyanto, Okka; Maruf, Farid; Riduwan, Riduwan (Journal of Appropriate Technology for Community Services, 2025)
South Korea's Busan region is the second largest port area in South Korea, has a dynamic economic ecosystem with many industrial sectors that attract local and foreign youth. However, adapting to the work environment in Busan is a challenge, especially for young people who are new to this environment. The competitive and highly disciplined work culture in South Korea is often difficult for young people in the Busan area to adapt to. Ergonomic injuries are a common problem in the productive age group. Activities in the industrial, education, and technology sectors increase the risk of injury due to inappropriate work postures. Frequently repetitive work by productive workers can cause musculoskeletal disorders such as back, neck, and wrist pain, which have an impact on work productivity. Unfortunately, youth awareness of the importance of ergonomics is still low. Therefore, socialization regarding ergonomic injuries is needed to increase youth awareness and understanding of the risks and how to prevent them. This activity includes education on correct work postures, adjustments to the workplace, and stretching practices after work to reduce muscle tension. The results of the implementation showed an increase in participants' understanding and their interest in applying ergonomic principles in everyday life. This activity succeeded in increasing understanding from 30% to 100% of participants meeting the criteria for basic understanding of ergonomics.